Motivation and Parenting Class untuk Meningkatkan Motivasi Belajar Peserta Didik Dan Wali Siswa SD - Kumala, Farida Nur; Rahayunita, Cicilia Ika; Rahayu, Sri; Huda, Rofiul; Setiawan, Dwi Agus (FKIP Universitas Sebelas Maret, 2023)
Community service activities aim to increase motivation and help parents in parenting. The method consists of several stages: (1). Counseling for parents by motivating parents to support their children's learning, material delivery activities, sharing sessions, ending with questions and answers, (2). Counselling for students, mainly grades 5 and 6, who will face exams to be motivated to study harder. The activities consist of delivering motivational materials for students, question and answer activities, and writing letters to their parents containing the goals that students want to achieve. Implementing the motivation and parenting classes goes according to the planned program. Parents and students were enthusiastic about participating in this training. Some suggestions include the need for regular mentoring activities, bearing in mind the limited knowledge of the community regarding parenting because parents are the first and primary source of education for children.